INDUSTRI BERBASIS SINGKONG DI DESA CITATAH, KECAMATAN CIPATAT, KABUPATEN BANDUNG BARAT - Dian Sepiati; Siska Siska; Febby Fitri Yolanda; Rizki Oktaviandra; Resma Yani; Agusti Handoko; Widya Meisya Hardin; Popy Ariani; Ananta Wijaya; Bima Aulia Fikri; Sri Mariya (JURUSAN GEOGRAFI FIS UNP, 2020)
Peuyeum is a special food in West Java regency whose main raw material is cassava. Citatah Village is one of the villages in West Bandung regency which is the center of cassava peuyeum processing. Data obtained from interviews, observations and questionnaires. The method used in this research is quantitative descriptive method by describing the findings in the field. Both by using storytelling and visual thinking techniques, then depicting using a canvas model to illustrate the overall business of the Peuyem Industry. The result is that there is no innovation in processing peuyeum into other products that have a higher selling value.